The Reality of Translating and Employing Mathematical Symbols in the Arab Critical Field : The Example of Gérard Genette’s Diagram - حلفاوي محمد (LANGUAGE ART, 2025)
At times, critical language has included mathematical symbols, which were blended in to explain certain schematics or to illuminate some concepts that required detailed and precise explanation. These symbols, which rely on accuracy, encountered some differences in the process of transfer, translation, or even their handling within the Arab environment, as well as the presence of the Arabic text, which differs from the original text. Although the purpose for which these symbols were employed remains clear, the important question is: Did these translated symbols contribute to the course of critical analysis of texts? And how was their use in various critical studies? In line with this, this research paper investigates the methods of translating mathematical symbols used in the critical field, through focusing on Gérard Genette’s model, specifically his notion of time, where he employed it in one of its aspects: the four movements related to the speed of time. The paper highlights how the translation and use of language and the mathematical term employed in the diagram presented by Genette to measure the speed of narrative time were carried out. This research paper discusses the issue of translating these mathematical symbols between precision and awkwardness, and also examines instances where these translations stray from their original meaning, a responsibility attributed to the practical field. It underscores the necessity of ensuring accuracy in the translation of terms and calls for caution when transferring such information from its original environment to the Arabic one, ensuring the safety of the transfer and correctness of the translation.